Testicular Fine Needle Aspiration in Male Infertility: A Review (Journal of Chittagong Medical College Teachers' Association, 2011)
Key words: fine needle aspiration; cytology; testis; infertility; asoozpermiaDOI: 10.3329/jcmcta.v21i1.7681 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):62-65